Strength and consolidation behaviour of remolded Redbed claystone from the Mae Moh Lignite Mine - Dongol, Abhishek, author; Bareither, Christopher, advisor; Chao, Kuo-Chieh, advisor; Scalia, Joseph, IV, committee member; Gallen, Sean, committee member (Colorado State University. Libraries, 2024)
The objective of this study was to evaluate the strength and consolidation behavior of remolded Redbed claystone within a critical state framework. In 2018, a slope failure occurred in the northwestern waste rock pile at the Mae Moh Lignite mine in Thailand. A hypothesis of the failure was the slaking of the claystone at the base of the piles resulted in substantial strength loss relative to the intact blocky mass of the as-placed claystone waste rock. Consolidated undrained (CU) triaxial compression tests were conducted on 38-mm-diameter samples of remolded and intact specimens of the claystone. Remolded specimens were prepared from slurry and consolidated to form normally consolidated clay specimens. One dimensional consolidations test were conducted on remolded and intact claystone specimens prepared in a similar manner. The remolded specimens exhibited contractive, strain-softening behavior in undrained shear typical of normally consolidated clays with effective friction angles ranging between 20° and 21° (M = 0.8). The intact claystone exhibited stiff, dilative behavior in undrained compression with higher shear strength parameters (M = 1.11-1.66). One dimensional consolidation tests on remolded specimens yielded only virgin compression, whereas similar tests on in-tact specimens yielded only negligible recompression. The claystone transitioned from a strong, stiff, dilative material to a soft, contractive soil with a drastic reduction in strength and an increase in compressibility. A modified Cam Clay model was parameterized from the triaxial and consolidation results to model the shear behavior of remolded Redbed claystone. The model predictions showed good agreement with observed laboratory test data, which supports the use of the model to in advanced stress-deformation modeling of the waste rock piles at Mae Moh Lignite Mine.
Strength and consolidation behavior of remolded Redbed claystone from the Mae Moh Lignite Mine
Keywords: critical state soil mechanics; slaking; fully softened strength; claystone